FEATURES OF THE DETERMINATION OF INSOLVENCY ENTERPRISES IN CRISIS MANAGEMENT IN AUSTRIA - Yury A. Arutunov (Вестник Российского экономического университета имени Г. В. Плеханова)
Market reforms in conditions of tough competition results in insolvency of some business entities or their temporary inability to pay. The article investigates the notion of managing insolvent enterprises which is illustrated by experience of Austrian commercial organizations. Factors affecting the efficiency of the process are shown. The author identifies features of bankruptcy, analyzes preventive measures and situations of non-court settlement of crisis situations at the enterprise, describes initiation of the case and shows principle types of insolvency procedures. Categories of insolvency and over-indebtedness are identified which can give grounds for initiation of proceedings for bankruptcy.